Optimizing Artificial Intelligence Systems for Real-World Applications - Boya Marqas , Ridwan; Saman M. Almufty,; ENGİN AVCI, Prof. Dr.; R. Asaad, Renas (International Journal of Scientific World, 2025)
The optimization of Artificial Intelligence (AI) systems is critical for improving performance, scalability, and adaptability across various real-world applications. This paper explores key optimization techniques, including algorithmic enhancements, hardware acceleration, software tools, and data preprocessing. Challenges such as resource constraints, domain-specific requirements, and ethical concerns are analyzed. Case studies in healthcare, finance, manufacturing, and autonomous systems demonstrate notable improvements in accuracy, efficiency, and scalability. A systematic framework is proposed to guide AI optimization, incorporating iterative testing, hardware-software integration, and deployment strategies. The findings highlight AI optimization’s transformative potential in developing scalable, efficient, and ethical systems. Future research directions include the creation of generalizable frameworks, energy-efficient AI, and fairness-aware optimization to ensure broader applicability and equity.